Cover Image, Volume 73, Issue 8. Issue 8 (3rd July 2017) - Young, Stephen L
Abstract : The cover image, by Stephen L Young, is based on the Perspective A systematic review of the literature reveals trends and gaps in integrated pest management studies conducted in the United States, DOI:10.1002/ps.4574 . Design Credit: Kevin Judd, Northeastern Integrated Pest Management Center, Cornell University. Abstract : The cover image, by Stephen L Young, is based on the Perspective A systematic review of the literature reveals trends and gaps in integrated pest management studies conducted in the United States, DOI:10.1002/ps.4574 . Design Credit: Kevin Judd, Northeastern Integrated Pest Management Center, Cornell University.